PENGARUH ROA, CAR, NPL, LDR, BOPO TERHADAP NILAI PERUSAHAAN BANK UMUM - Sundus Nur Halimah; Euis Komariah (Politeknik Negeri Batam, 2017)
This study aims to determine Effect of ROA, CAR, NPL, LDR, and BOPO partially and simultaneously on Firm Value. Samples were Commercial Bank Go Public is listed on the Indonesia Stock Exchange from 2011 to 2015 by using purposive sampling method. There are 25 Commercial Banks that qualify as research samples. The method of analysis in this research is multiple linear regression analysis. The results of this study show that ROA, CAR, and LDR significant effect on Firm Value, NPL and BOPO no significant effect on Firm Value. Simultaneously these variables significant effect on Firm Value.